Māori leadership : affecting positive change within primary education : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Education at Massey University, Palmerston North, Aotearoa New Zealand - Wood, Andrew (Massey University, 2009)
This thesis sought to examine the nature of Māori leadership within the context of English medium primary education. It sought to identify whether a style of leadership that was unique to Māori existed and whether or not the identified style or styles reflected in contemporary times in schools are underpinned and informed by values, practices and ideals inherent within Māoridom. Many aspects of Māoridom have not only endured despite the effects of colonisation but have in fact survived and flourished. Māori leadership is one such aspect. The findings reflect strong styles where values, ideals and practices which are strongly emphasised within Māoridom have all had an informing role for the participant leaders. The leadership styles, approaches and strategies identified within this study echo those of the past. In using the identified strategies, the Māori school leaders have facilitated the development of an educational environment and culture that is empowering and productive in making a positive difference for every child in the school and for the staff, parents and whanau of the school.
Keywords: Māori; Kura tuatahi; Education; Educational leadership